Caste and Equality in India A Historical Anthropology of Diverse Society and Vernacular Democracy - Tanabe, Akio (Routledge New Horizons in South Asian Studies, 2022)
This book presents an alternative view of caste in Indian society by analysing caste structure and change in local communities in Orissa from historical and anthropological perspectives. Focusing on the agricultural society in the Khurda district of Orissa between the eighteenth century and 2019, the book links discussions on the current transformation of society and politics in India with analyses of long-term historical transformations. The author suggests that, beyond status and power, there is another value which is important in Indian society, namely ontological equality, which functions as the politico-ethical ground for asserting respect and concern for the life of others. The book argues that the value of ontological equality has played an important role in creating and affirming the diverse society which characterises India. It further contends that the movement towards vernacular democracy, which has become conspicuous since the second half of the 1990s, is a historically groundbreaking event which opens a path beyond the postcolonial predicament, supported by the affirmation of diversity by subalterns based on the value of ontological equality. This important contribution to the study of Indian society will be of interest to academics working on the social, political and economic history, sociology, anthropology and political science of South Asia, as well as to those interested in social and political theory.